GP 2003 - Språkbanken Text (University of Gothenburg, 2024)
A corpus with texts from Göteborgsposten

En korpus med texter från Göteborgsposten
GP 2003
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik